KEBIJAKAN MONETER DAN INVESTASI PORTFOLIO ASING - Fajarini, Dian; Nirmala, Tiara; Purwaningsih, Vitriyani Tri (Jurnal Ekonomi dan Bisnis Nias Selatan, 2023)
Foreign portfolio investment is one of the components to support economic activity in a country. On the other hand, policies and economic conditions in a country are considered to have an influence on foreign portfolio investment flows and so does Indonesia. Thus, this paper aims to analyze the influence of monetary policy, namely interest rates, macroeconomic conditions, namely exchange rates and economic growth and capital market conditions, namely the composite stock price index on Indonesia’s foreign portfolio investment. The object of this research is to 11 countries that have foreign portfolio investments in Indonesia for the period Q2:2017 – Q1:2021 using panel data regression. The research results obtained show that interest rates and exchange rates have a positive and significant effect on foreign portfolio investment. Meanwhile, the composite stock price index and economic growth have no significant effect on foreign portfolio investment in Indonesia.